2011
DOI: 10.1007/s10059-011-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs for Tissue Culture Response in Soybean (Glycine max (L.) Merr.)

Abstract: Quantitative trait loci (QTLs) that control the tissue culture response in soybean were detected by using 184 recombinant inbred lines (RILs) derived from two varieties: Kefeng No.1 and Nannong 1138-2. The molecular map consisting of 834 molecular markers using this population covered space 2307.83 cM of the genome throughout 24 linkage groups. The performance of tissue culture in soybean was evaluated by two indices: callus induction frequency (CIF) and somatic embryos initiation frequency (SEIF). They were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Several studies have targeted the genetic control of in vitro responsiveness in a variety of plants. Many have involved QTL identification [34,65,[79][80][81][82][83], and more recently, GWAS [31,36,84]. These studies have identified several genetic loci and candidate genes associated with various aspects of in vitro responsiveness.…”
Section: Albino Regenerationmentioning
confidence: 99%
“…Several studies have targeted the genetic control of in vitro responsiveness in a variety of plants. Many have involved QTL identification [34,65,[79][80][81][82][83], and more recently, GWAS [31,36,84]. These studies have identified several genetic loci and candidate genes associated with various aspects of in vitro responsiveness.…”
Section: Albino Regenerationmentioning
confidence: 99%
“…It is believed that genetic control of plant regeneration ability could be either qualitative (Reisch and Bingham 1980 ) or quantitative (Taguchi-Shiobara et al 2006 ). A large number of studies have been reported on quantitative trait loci (QTLs) analysis for tissue culture response (TCR) in soybean (Yang et al 2011 ), rice (Li et al 2013a ; Nishimura et al 2005 ; Zhao et al 2009 ), maize (Murigneux et al 1994 ; Wan et al 1992 ), barley (Bregitzer and Campbell 2001 ; Manninen 2000 ; Mano and Komatsuda 2002 ), rye (Bolibok et al 2007 ), and wheat (Jia et al 2007 ; Nielsen et al 2015 ; Torp et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Especially due to the advanced sequencing technique, much more gene-based molecular markers could be exploited from transcriptome data from massively-parallel next-generation sequencing (NGS) (Lu et al, 2011;Metzker, 2010). Researchers have benefited from the availability of techniques for the rapid and costeffective development of molecular marker-based linkage maps (Yang et al, 2011). Four genetic maps were provided on Solanaceae Genomics Network (http://solgenomics.net/), of which pepper-FAO3 contained the most 720 markers with an averaged 1.89 cM interval (Mueller et al, 2005).…”
Section: Introductionmentioning
confidence: 99%